Outcome evaluation of Active Herts: A community-based physical activity programme for inactive adults at risk of cardiovascular disease and/or low mental wellbeing - Chater, Angel M.; Schulz, Joerg; Jones, Andy; Burke, Amanda; Carr, Shelby; Kukucska, Dora; Troop, Nick; Trivedi, Daksha; Howlett, Neil (Frontiers in Public Health, 2022)
Background: A high proportion of UK adults are inactive, which can lead to a range of physical and mental health concerns. Active Herts is a community-based physical activity programme for inactive adults at risk of cardiovascular disease and/or low mental wellbeing. This paper provides a pragmatic evaluation of this programme. Method: This longitudinal study observed 717 adults (68% female, mean age = 56.9 years) from the ‘Active Herts’ programme. Programme users were provided with a 45-minute consultation with a ‘Get Active Specialist’, who talked them through an Active Herts self-help booklet and then signposted them to free or subsidised local exercise sessions. Programme users were followed up with a booster call two weeks later. The Get Active Specialist was a registered exercise professional (REPS Level 3), with additional training from the study team in motivational interviewing, health coaching, COM-B behavioural diagnosis and delivery of behaviour change techniques (BCTs) in practice. The Active Herts booklet contained theoretically-driven and evidence-based BCTs to translate behavioural science into public health practice. Physical activity (Metabolic Equivalent Time [METs], measured using the International Physical Activity Questionnaire (IPAQ), perceived health (EQ-5D-5L) and mental wellbeing (Warwick-Edinburgh Mental Wellbeing Scale: WEMWBS) were measured at baseline, three, six and twelve months. Results: At the end of the 12-month programme, users showed sustained improvements in physical activity (by +1331 METS), exceeding weekly recommendations. Sitting (reducing by over an hour per day), sporting participation, and perceptions of health were also improved, with improvements in mental wellbeing in the first three months. Conclusion: Designing and delivering a community-based physical activity programme that is theoretically-driven and evidence-based with frequent behaviour change training and supervision can yield a significant increase in self-reported physical activity, reduction in sitting behaviour and improvements to perceived health and mental wellbeing. Future research should extend this approach, utilising a real-world, pragmatic evaluation. Trial registration: ClinicalTrials.gov identifier (NCT number): NCT03153098